YOUTUBE DAN TRANSFORMASI SOSIAL DIGITAL DI INDONESIA: ANALISIS LINTAS SEKTOR PENDIDIKAN, SOSIAL, POLITIK, DAN EKONOMI - Eva Riyanty Lubis; Lola Sapriani Hasibuan; Ahmad Sultoni Matondang; Rosmayani Rambe; Sholeh Fikri (Program Studi Komunikasi dan Penyiaran Islam, 2026)
YouTube has evolved into a digital platform that influences various sectors of social life. However, academic studies in Indonesia still tend to examine its impacts in a fragmented and sector-specific manner. This study aims to synthesize previous research findings in order to understand YouTube’s cross-sectoral role in education, social life, politics, and the economy in Indonesia. This research employs a qualitative approach using an integrative literature review method, drawing on accredited national journal articles and reputable international journals published between 2018 and 2025. The findings indicate that YouTube functions as a digital social infrastructure that expands access to learning, facilitates identity expression and alternative public spheres, shapes attention-driven political communication, and supports the growth of a content-based creative economy. Nevertheless, the literature also highlights structural risks, including gaps in digital literacy, social polarization, political disinformation, and inequality among content creators, all of which are interconnected through algorithmic mechanisms and the attention economy. This study contributes conceptually by proposing a cross-sectoral analytical framework that links algorithms, attention, and monetization as the central mechanisms of YouTube-driven digital social transformation, while also offering implications for strengthening digital literacy and media policy in Indonesia.